(untitled) (LEARNing Landscapes, 2012)
There is typically no expectation of creativity in the context of teacher professional development programs. Yet, the Common Core Curriculum and other constructs demand that teachers exhibit considerable creativity in curriculum and instruction. The challenge then for teacher educators is to support each learner’s individual growth toward greater cognitive complexity. This research examined the experience of a group of P-12 classroom teachers who explored the use of the arts to nurture their own creative processes, classroom research, understanding of difference, particularly race and culture, and instructional practices in the context of a graduate teacher professional development program.